Recycled Concrete Aggregates as a Filter for Removal of Phosphorus in Synthetic Wastewater - Roni, Norwardatun Abd; Adnan, Suraya Hani; Hamdan, Rafidah (International Journal of Engineering and Technology, 2018)
This paper assesses of recycled concrete aggregates as a filter for removal of phosphorus in synthetic wastewater. Recycled concrete aggregate used as a filter system emerged as an alternative technology for phosphorus removal. This can overcome the problem of construction site waste by converting the waste into something valuable products. Thus, this study aim to determine the percentage of Phosphorus removal by using two different size of Recycled Concrete Aggregate which is (5 mm to 10 mm) and (25 mm to 30 mm). A total of five vertical recycled concrete aggregate filter laboratory scale was design using recycled concrete aggregate and five different concentration of synthetic wastewater which is 10 â€“ 50 mg/L was prepared. Samples were taken from the influent and effluent filters to be tested once a week, and analyzed to determine the value of pH and the percentage of Phosphorus removal (%). RCA was analyzed using Scanning Electron Microscopy (SEM) and Energy-dispersive X-ray spectroscopy (EDX) testing to determine chemical composition. Results shows that RCA is highly contained with Aluminium, Calcium and Magnesium elements that enhanced the phosphorus adsorption. The RCA with size 5 mm to 10 mmÂ and synthetic wastewater 10 mg/L display high potential in removing Phosphorus with 99.54% removal at pH 9.77. The lower concentration of synthetic wastewater, smaller size of RCA and higher pH have slightly better Phosphorus removal efficiency. Thus, RCA has a potential in removing Phosphorus from synthetic wastewater.